2013
DOI: 10.1111/nmo.12109
|View full text |Cite
|
Sign up to set email alerts
|

An oropharyngeal pH monitoring device to evaluate patients with chronic laryngitis

Abstract: Oropharyngeal pH monitoring appears to be more sensitive than traditional pH monitoring in evaluation of patients with extraesophageal reflux. It is a promising tool in evaluation of this difficult group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 20 publications
0
22
0
1
Order By: Relevance
“…For the diagnostic investigation of extra-oesophageal presentation, dual-channel (pharynx and 5 cm above the lower oesophageal sphincter) or multichannel (pharynx, proximal oesophagus, 5 cm above lower oesophageal sphincter) monitoring has been proposed. A newly developed pharyngeal pH monitoring has reported higher sensitivity 44. Reflux monitoring can be further coupled with intraluminal pressure sensor monitoring to detect cough episodes in order to determine the chronological relationship between reflux and suspected extra-oesophageal symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…For the diagnostic investigation of extra-oesophageal presentation, dual-channel (pharynx and 5 cm above the lower oesophageal sphincter) or multichannel (pharynx, proximal oesophagus, 5 cm above lower oesophageal sphincter) monitoring has been proposed. A newly developed pharyngeal pH monitoring has reported higher sensitivity 44. Reflux monitoring can be further coupled with intraluminal pressure sensor monitoring to detect cough episodes in order to determine the chronological relationship between reflux and suspected extra-oesophageal symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…30 In a recent study using the same pH probe as this study, a nasopharyngeal pH cutoff of 6 correlated with symptoms of SERD. 32 Most clinicians do not have a means of directly measuring overnight pharyngeal pH and so, in practice, must decide whether to treat empirically with antacids, suggest head-of-bed elevation, or do both. On the basis of our findings that 48% of patients with suspected SERD had confirmatory pharyngeal pH monitoring and 55% of those with positive studies had supine-only reflux, one can predict that approximately 26% of patients referred to an allergy clinic with suspected SERD will have supine-only reflux.…”
Section: Discussionmentioning
confidence: 99%
“…One prospective observational study in healthy volunteers developed normative data for this device at pH cutoff of 4, 5 and 6 for the distal esophagus and oropharynx [81]. Significantly higher number of reflux events has been detected by Restech pH in LPR patients than patients with GERD and healthy volunteers concluding that the device may hold promise in evaluation of those with suspected GERD related LPR [80,82]. From a surgical standpoint, an abnormal Restech pH was associated with 90% of patients who have extra-esophageal GERD symptoms that were improved with antireflux surgery; whereas a negative Restech study more reliably indicated the absence of reflux-induced extra-esophageal symptoms [83].…”
Section: Diagnostic Considerationmentioning
confidence: 94%
“…A comparison of this device to the traditional pH catheters has shown faster detection rate and faster time to equilibrium pH [80]. One prospective observational study in healthy volunteers developed normative data for this device at pH cutoff of 4, 5 and 6 for the distal esophagus and oropharynx [81].…”
Section: Diagnostic Considerationmentioning
confidence: 98%